2021
DOI: 10.3390/electronics11010020
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of VTOL Operated Intercity Electrical Vehicle for Urban Air Mobility

Abstract: This paper discusses the conceptual design of an intercity electrical vertical take-off-and-landing aircraft. A literature survey of existing eVTOL aircrafts, configuration selection, initial sizing, weight estimation, modelling and analysis was conducted. The present intercity eVTOL aircraft has the capability to carry four passengers along with one pilot for a distance of 500 km. Two specific aircraft modes, such as air-taxi and air-cargo mode, are considered in the present design. Market entry is predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Lee et al (2020) found that the MTOW has a direct effect on aircraft performance in terms of range, cruise speed, and stall speed (Lee, Tullu, & Hwang, 2020). Akash et al (2022) presented the design of a TR eVTOL aircraft that they expect to carry 500-kilograms of payload for 500 kilometers by assuming the use of a 600 Wh/kg lithium-sulphur battery (Akash, et al, 2022). Their mission profile estimated that cruising at 200 km/h will account for 81% of the total energy use.…”
Section: Flight Range Projectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al (2020) found that the MTOW has a direct effect on aircraft performance in terms of range, cruise speed, and stall speed (Lee, Tullu, & Hwang, 2020). Akash et al (2022) presented the design of a TR eVTOL aircraft that they expect to carry 500-kilograms of payload for 500 kilometers by assuming the use of a 600 Wh/kg lithium-sulphur battery (Akash, et al, 2022). Their mission profile estimated that cruising at 200 km/h will account for 81% of the total energy use.…”
Section: Flight Range Projectionsmentioning
confidence: 99%
“…The lift generated is the perpendicular component of the vector sum of all the forces that the air exerts on the airframe while flowing around it. The CL factor scales the dynamic pressure to create the lifting force, but it has been difficult to calculate (Akash, et al, 2022). Therefore, engineers estimate CL by measuring the dependent factors.…”
Section: Flight Physics Reviewmentioning
confidence: 99%
“…This article discusses a thorough strategy for the entire project and the creation of an energy planning solution for hybrid drivetrains founded on Q-learning [47]. The prototype model of an interstate electric vertical take-off and landing (VTOL) airplane is discussed in this study [48]. A novel hybrid energy infrastructure is proposed in this study to increase the shifting performance of HEVs [49].…”
Section: Evs Planningmentioning
confidence: 99%
“…An airport shuttle would provide scheduled flights between airports and strategic locations or points of interest (POI) in metropolitan areas for similar distance ranges as the air taxi service [23,24]. Finally, intercity scheduled services between cities would cover distances of more than 100 km and would allow direct access to POIs [25].…”
Section: Introductionmentioning
confidence: 99%